Polyethylene Improved Structural Properties During Production - Sirgiyevich, Rosilov Mansur; Komiljonovich, Sultonov Oybek (International Journal on Orange Technologies, 2023)
In connection with the expansion of the fields of application of polymeric materials and the condition of the conditions for their exploitation, the creation of materials with predetermined properties is becoming increasingly important. This can be realized through the synthesis of new, modified and industrial polymers.